2020
DOI: 10.1002/bbb.2109
|View full text |Cite
|
Sign up to set email alerts
|

Production routes of advanced renewable C1 to C4 alcohols as biofuel components – a review

Abstract: In 2018, the EU's revised Renewable Energy Directive came into force, increasing renewable energy targets for all energy sectors while limiting the use of first‐generation biomass as feedstock. Fuel components like methanol, ethanol, propanols, and butanols represent promising candidates to enable the targets for transportation to be achieved because they can be used with existing infrastructure and can be further processed to give additives and substitutes. A wide variety of feedstocks and processes are avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 269 publications
0
30
0
9
Order By: Relevance
“…An analysis of the sources cited showed that the spatial resolution used in the sources did not always fit the scope of the literature studied. This supports the assumption that suitable information on biomass supply costs or prices is not always available for use as input variables in the models, although assumptions about underlying supply costs and prices have a significant impact on model results [5][6][7]. Therefore, supply costs or prices are influenced by spatial effects, such as the amount of available biomass, as Brown et al [62] mentioned.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…An analysis of the sources cited showed that the spatial resolution used in the sources did not always fit the scope of the literature studied. This supports the assumption that suitable information on biomass supply costs or prices is not always available for use as input variables in the models, although assumptions about underlying supply costs and prices have a significant impact on model results [5][6][7]. Therefore, supply costs or prices are influenced by spatial effects, such as the amount of available biomass, as Brown et al [62] mentioned.…”
Section: Discussionmentioning
confidence: 53%
“…Techno-economic analyses are used, among other things, to evaluate whether it is economically feasible to employ products made from biogenic raw materials. The studies by Lepage et al, Schubert, and De Jong et al show that the input variables used in the analyses for the costs and prices of supplying the biogenic raw materials can have a significant influence on the models' findings [5][6][7]. For that reason, it is important for techno-economic models to use data on supply costs and prices for biogenic raw materials that are valid and fit the context of the research.…”
Section: Introductionmentioning
confidence: 99%
“…Propanols (n-PrOH, 2-PrOH) can be obtained by biochemical conversion of sugars and by catalytic hydrogenolysis of bioglycerol as an available by-product of biodiesel production that it is an attractive approach regarding sustainability and energy efficiency compared to the processes based on petroleumderived feedstocks. [42,43] However, the mixture of both propanols is formed in glycerol hydrogenolysis. The primary alcohols are poor H-donors in comparison with the secondary alcohols (Figure 5).…”
Section: Influence Of Primary Alcohol On Phenol Hydrogenationmentioning
confidence: 99%
“…Alcohols are also products from a conventional refinery, but their use requires fewer precautions and lower equipment costs since the reactors require less complexity because of the lower pressures. In the future, it is expected that both molecular hydrogen and alcohols can be obtained in biorefineries (Campos 2018;Schubert 2020). LA or LE CTH involves Meerwein-Ponndorf-Verley (MPV) reduction (Johnstone et al 1985).…”
Section: Gamma-valerolactone From Biomassmentioning
confidence: 99%